Histological and Histochemical study of the Esophagus in Laughing Dove Streptopelia senegalensis (Baghdad Science Journal, 2015)
The present study represent the histological and histochemical structure of the esophagus of laughing dove Streptopelia senegalensis, one of the wild birds, which feed on the seeds( grainvorous).The result showed that the esophagus long tubular quit wide and highly distensible organ situated at the right side of the nick , lie between pharynx and stomach it was divided into cervical and thoracic part , the cervical part longer than the thoracic part, and the crop was merely enlargement fusiform in shape which located at the entrance of the thorax. Esophagus parts showed that composed of four layer ;the mucosa, sub mucosa, muscular and adventitia or serosa, the mucosal layer was arranged in folds which was longer in the cervical part and constituted by nonkertenized stratified squamous epithelium ,the lamina propria had esophageal glands in the the thoracic part only .The submucosa composed of a thin layer of connective tissue , muscularis externa consists of two layers of smooth muscle fibers, which were an inner circular layer and an outer longitudinal layer which was surrounded by adventitia or serosa .The histochemical result showed the glands positive reaction with (PAS) dye and the mucous layer of the wall of the esophagus showed positive with Alcian blue -PAS dye as well as with Mercuric bromophenol blue dye, esophageal glands did not show a positive reaction with the last dye.